The Behaviour of Trading Volume : Evidence from Money Market Instruments - Faniband, Muhammadriyaj (Indian Journal of Finance, 2020)
This paper analyzed the impact of macro and non-macroeconomic factors on the trading volume of the certificate of deposits and commercial paper with regard to India during the monthly period from April 2012 – March 2018 using the quantile regression approach. The results revealed that gross domestic product rate, Consumer Price Index, Economic Policy Uncertainty Index, the Volatility Index, and the Nifty index had a negligible impact on the trading volume of corporate bonds. However, interest rates and exchange rates did not influence the trading volume of corporate bonds. In the other context, gross domestic product rate, Consumer Price Index, interest rates, the Volatility Index, and movements in the Nifty index showed a negligible impact on the trading volume of commercial paper. However, the variations in the trading volume of commercial papers were not explained by exchange rates and Economic Policy Uncertainty Index.